Investigation of the translaminar fracture behavior of the fiber-reinforced composites stitched perpendicular to their plane - Asan, Ahmet Murat; Kaman, Mete Onur; Dag, Serkan; Erdem, Serkan; Turan, Kadir (Springer Heidelberg, 2024)
To increase the fracture toughness, the two-dimensional laminated textiles can be stitched with fibers throughout their thickness. But the stitch properties effect the mechanical behavior of the composite plates. Because of this reason, in this study, translaminar toughness of carbon fiber composites stitched with different densities and angles is investigated for the first time, experimentally and numerically. In the experimental study, fracture tests are performed according to ASTM E1922 standard and critical load; crack tip opening displacements and fracture toughness values are determined. In the numerical study, the critical stress intensity factor is determined using the M-integral method and the displacement correlation method. Modeling and fracture toughness analyses are performed in ANSYS finite element package. In order to find the crack propagation directions numerically, the model prepared in ANSYS is transferred to the LS-DYNA program and progressive failure analysis is performed. Stitching the layered composites perpendicular to the plane has increased the fracture toughness by 23.5-80.6% for plain-woven composites and 1.41-9.38% for UD composites. Fracture toughness values have increased with increasing stitch density. This increase is highest in the specimen stitched in the longitudinal direction where the toughness increased by similar to 15.4% with 100% increase in stitch density. The highest fracture toughness is obtained with double-directional stitching with a stitch density of 1.25 mm. It is determined that the designed heterogeneous model gives more accurate results than the homogeneous model by similar to 1-6%.
Keywords: Stitch; M-integral; Translaminar fracture toughness; Laminated composites; Progressive failure analysis